Share of exports to low-income countries, productivity, and innovation: A replication study with firm-level data from six European countries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
Crinò and Epifani (2012) report and discuss two empirical regularities they find in a representative sample of Italian manufacturing firms. First, there is a negative correlation between firms' productivity and their export share to low-income destinations. Second, there is a negative correlation between firms' innovation activity and their export share to low-income destinations. This note uses recently available comparable high quality firm level data for six European countries (including Italy) and similarly specified empirical models in an attempt to replicate these results. Replication failed completely. The link found between the share of exports to lowincome countries and either productivity or R&D intensity is never in line with the results from Crinò and Epifani (2012).
Keywords: F14; 330; exports; low-income destinations; productivity; innovation; EFIGE data